ANALISIS PENGARUH PENDAPATAN PADA INDUSTRI KERAJINAN DULANG FIBER DI DESA BRESELA, KABUPATEN GIANYAR - Putra, I Ketut Yasa; Sudiana, I Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2020)
The handicraft industry has an important role in Bali apart from being one of supporting sectors economy Bali. One of them production Dulang Fiber in Bresela Village, Payangan District, Gianyar which is influenced several variables such as wage levels and worker skills. The research objectives 1) analyze the effect of the level of wages and workers' skills on the productivity of the Dulang Fiber industry in Bresela Village, 2) analyze the effect of wage levels, worker skills and productivity on the income of the Dulang Fiber industry in Bresela Village, 3) analyze the role of productivity to mediate the effect of wage levels and workers' skills towards Dulang Fiber industry income in Bresela Village. Data used primary data. Method determining sample using census method with sample 65 units. Data analysis technique used path analysis. Results this study 1) the level of wages and workers 'skills has a positive and significant effect on industrial productivity, 2) the level of wages, workers' skills, and productivity has a positive and significant effect on industrial income. 3) Productivity mediates the relationship between wage levels and workers' skills on the Dulang Fiber industry income in Bresela Village.   Keywords: productivity, wage level, job skills, income